Valley-Confinement and River-Tidal Controls on Channel Morphology Along the Fluvial to Marine Transition Zone of the Ðồng Nai River System, Vietnam - Gugliotta, Marcello; Saito, Yoshiki; Ta, Thi Kim Oanh; Nguyen, Van Lap (Frontiers in Earth Science, 2019)
Along the fluvial to marine transition zone (FMTZ) of river deltas, the river-tidal dynamics exert a primary control on channel width, sinuosity, and bed elevation; however, other local factors, such as valley confinements, bifurcations, and confluences, can modify the channel morphology. Here, we report a case study of the major channel of the Ðồng Nai River System (DNRS) that shows complex morphological trends linked to multiple factors. This study is based on the analysis of satellite images and bathymetric maps of the studied channel, together with a digital elevation model of the area and additional climate and hydrology data. Our study shows that channel width, sinuosity, and bed elevation show mutual relationships and complex upstream to downstream trends linked to the river-tidal dynamics and valley confinements, together with more local effects due to bifurcations and confluences. The tidal dynamics is mainly responsible for the seaward-widening and seaward-shallowing trends and the abrupt decrease in channel sinuosity observed in the downstream tract of the channel, whereas the relatively constant channel width and sinuosity in the upstream tract suggest a control of the river dynamics. The studied channel also shows three areas of valley widening or exit, which are characterized by high channel sinuosity, the presence of minor and major bifurcations, and additional changes in channel width and bed elevation, and they are considered important nodes in this system. Valley-related nodes also show different active and inactive features, implying that the degree of activity and importance of these nodes likely varied through time, migrating from upstream to downstream due to the deltaic progradation.